Microplastics as an emerging source of particulate air pollution: A critical review - Sridharan, Srinidhi; Kumar, Manish; Singh, Lal; Bolan, Nanthi S.; Saha, Mahua (Journal of hazardous materials, 2021)
Accumulation of plastic litter exerts pressure on the environment. Microplastics (MPs) pollution has become a universal challenge due to the overexploitation of plastic products and unsystematic dumping of plastic waste. Initial studies on MPs and their implications had been confined to aquatic and terrestrial ecosystems, but recent research has also focused on MPs in the air. Their impacts on urban air quality and atmospheric transport to pristine habitats have emerged to be a serious concern. However, the extent and the significance of impacts of airborne particulate matter (PM) MPs on human health are not clearly understood. Further, the influence of airborne MPs on indoor and outdoor air quality remains unknown. We highlight the human health impacts of airborne PM-MPs with a special focus on the occupational safety of the industry workers, their possible influence on Air Quality Index (AQI), their potential exposure, and accumulation in the canopy/arboreal, above-canopy and atmospheric (aerial) habitats. The present review emphasizes the data limitations and knowledge gaps on the atmospheric transport and contribution of particulate plastics to the worsening of overall urban air quality and throws critical perspectives on whether atmospheric MPs pollution is trivial or an actual matter of concern. [Display omitted] •Canopy and emergent layer ecosystems are highly vulnerable to airborne microplastics.•No datum on the influence of microplastics on the visibility and air quality index.•Airborne microplastics may contribute to the overall particulate matter pollution.•Extensive studies on the occupational hazards of inhalable microplastics are needed.•Possible airborne transmission of COVID-19 by microplastics demands research.